The Assessment and Supervision of China’s Systemically Important Insurers - wang, da (Advances in Social Sciences Research Journal, 2016)
On July 19, 2013, the International Association of Insurance Supervisors (IAIS) announced the first list of Global Systemically Important Insurers (G-SII). Ping An Group, a China’s insurance company, is the only insurer coming from the Asian-Pacific region. The entrance of Ping An brought wide attention and research on the problem of systemically importance in China. This research is studying the systemic importance of 9 insurance groups in China. Basing on the financial data of the 9 insurance groups, this paper calculates the weight using the Entropy Method, and ranks the 9 insurance groups by using the Index Method. Meanwhile, this paper comes up with some proposals for the assessment and supervision of China’s Systemically Important Insurers to promote the stable development of the insurance industry and the whole financial system.